New technology and health meeting Asia's nutrition and food safety challenges (2007)
Technological trends in human food supply evolved from food security demands for nutritional quality and food safety, primarily driven by increased consumer awareness and involvement amidst escalating food and water-related health problems. Increased human immunodeficiency, extensive migration and travel, changing lifestyle of the population, ecological changes, and revolution in agricultural practices as well as food processing and distribution, and testing methodologies/technologies all contribute to amplifying the reality of foodborne diseases. Although foodborne diseases are a global concern, developing countries share the bigger brunt of the problem, symptomatic of underlying food and nutrition safety challenges in the region. This phenomenon has direct economic and political implications especially with the increasing food supply interdependence between and among countries. With the impact of globalization and free trade presently manifested on food safety, the current government affairs become critical and important to harmonize Asian export regulations in certain food products, to adopt international food and nutrition safety standards, and to remain active contributors in meeting of the Codex Alimentarius on organic farming, animal feeding, biotechnology, and probiotics. The Asian food industry sector is coping up with market competitiveness by keeping abreast with technological advances to ensure food safety throughout the "farm-to-table" food chain. Asian countries, however, need to strengthen their food and nutrition safety legislative and regulation systems, enhance the integration of initiatives from the different fields of science and various stakeholders, improve their technical capability on risk assessment and surveillance, and optimize information exchange systems. Meeting the challenges need strong political will among various stakeholders in the food supply chain, e.g. the science community, agricultural producers, food manufacturers and retailers, food service establishments, the government legislators/regulators/enforcers, the academe, media, and consumer advocacy groups.